KAJIAN EKSTRAK ETANOL BUNGA BOGENVIL (Bougenvillea spectabillis Willd) SEBAGAI BIOINDIKATOR ASAM BASA - Nurhaeni Nurhaeni; Fitri A Bande; Rismawaty Sikanna (KOVALEN: Jurnal Riset Kimia, 2017)
Studies of ethanol extract of bougainvillea flowers (Bougenvillea spectabillis Willd) as bioindicators of the acid-base has been done. The aims to determine the content of chemical compounds contained in extracts of bougainvillea flowers and bougainvillea flower extract pH stretch. Achievement of the objectives has done through the test of ethanol extract of bougainvillea identification of compounds and the determination of the acid-base stretch of pH indicator is. The obtained results showed that bogenvil ethanol extract containing flavonoids with 401 nm absorption and provided a color change in the acid and alkaline condition the color is yellow. The appropriate acid-base titration is used as bioindicators of a strong acid titration with a strong base, weak acid with a strong base and a weak base with a strong acid.Keywords: Flowers bougainvillea, indicators, bases acid titration